2020
DOI: 10.1039/d0mt00092b
|View full text |Cite
|
Sign up to set email alerts
|

Development of a metalloproteomic approach to analyse the response of Arabidopsis cells to uranium stress

Abstract: Elaboration of a top-down proteomic, biochemical and ionoproteomic toolbox to gain insights into the impact of uranyl (U) on Arabidopsis cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 63 publications
2
10
0
Order By: Relevance
“…The accumulation of U in the apoplast, which is a temperature-insensitive adsorption and diffusion process (Barberon and Geldner, 2014), accounts for 60-70% bioaccumulated U. This is in agreement with previous experiments showing that plant roots or plant cells exposed to U accumulate the radionuclide principally in the cell wall and intracellular spaces (Laurette et al, 2012a;Laurette et al, 2012b;El Hayek et al, 2018;El Hayek et al, 2019;Lai et al, 2020;Sarthou et al, 2020;Wu et al, 2020). The absorption of U by the symplastic pathway, which is mainly temperature-sensitive (reduction of energy metabolism, enzymatic activities, membrane fluidity, plasmodesmatal permeability) (Barberon and Geldner, 2014;Sager and Lee, 2014), accounts for 30-40% bioaccumulated U, and is virtually fully inhibited by external Ca at high concentration (Figure 3) or by inhibitors of NSCCs and Ca 2+ -permeable cation channels (Figure 4).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The accumulation of U in the apoplast, which is a temperature-insensitive adsorption and diffusion process (Barberon and Geldner, 2014), accounts for 60-70% bioaccumulated U. This is in agreement with previous experiments showing that plant roots or plant cells exposed to U accumulate the radionuclide principally in the cell wall and intracellular spaces (Laurette et al, 2012a;Laurette et al, 2012b;El Hayek et al, 2018;El Hayek et al, 2019;Lai et al, 2020;Sarthou et al, 2020;Wu et al, 2020). The absorption of U by the symplastic pathway, which is mainly temperature-sensitive (reduction of energy metabolism, enzymatic activities, membrane fluidity, plasmodesmatal permeability) (Barberon and Geldner, 2014;Sager and Lee, 2014), accounts for 30-40% bioaccumulated U, and is virtually fully inhibited by external Ca at high concentration (Figure 3) or by inhibitors of NSCCs and Ca 2+ -permeable cation channels (Figure 4).…”
Section: Discussionsupporting
confidence: 91%
“…Biochemical, molecular and metabolomic studies indicated that U triggers oxidative stress-related response pathways and perturbs hormones synthesis and signaling, primary metabolism, iron and phosphate assimilation pathways, and cell wall synthesis (Vanhoudt et al, 2011c;Vanhoudt et al, 2011a;Doustaly et al, 2014;Saenen et al, 2015;Tewari et al, 2015;Lai et al, 2020;Lai et al, 2021). Also, U has a significant impact on mineral nutrition, with important changes in some micro-and macronutrients concentration and distribution between roots and shoots (Misson et al, 2009;Vanhoudt et al, 2011b;Doustaly et al, 2014;Berthet et al, 2018;Lai et al, 2020;Sarthou et al, 2020;Lai et al, 2021;Rajabi et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…It is conceivable that the initial rapid increase was mainly due to biosorption, which tends to occur very quickly, since this process does not require the active uptake of the heavy metal into the cell, as indicated by a study involving green algae Chlorella vulgaris. 35 This statement is supported by Sarthou et al, 47 who showed that cell walls play an important role in binding U and thus contribute significantly to its immobilization. Rajabi et al 36 were able to show that after only 1 h of exposure, U(VI) was taken up by Nicotiana tabacum BY-2 cells.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…18,45,46 Another aspect of these studies pertains to mechanistic investigations of U uptake. Sarthou et al 47 cell wall, cell membranes, and external chelators represent a barrier for the uptake of U into Arabidopsis thaliana plant cells. However, this barrier can be surmounted such that toxic metals are taken up to a limited extent into these cells, thereby causing interactions with intracellular biomolecules.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Uptake of U through the iron assimilation pathways -Our study also suggests that U might enter the cell through iron transport systems. As for calcium, U and iron crosstalk is well documented in biological systems, particularly in plants where it was found that U interferes with iron homeostasis (Berthet et al, 2018;Doustaly et al, 2014;Sarthou et al, 2020;Vanhoudt et al, 2011). Also, several ferric iron-binding proteins were found to be able to bind U with high affinity, such as human transferrin, involved in iron transport to the bloodstream (Vidaud et al, 2007) and ferritin, an iron storage protein, from the archea Purrococus furiosus, the crayfish Procambarus clarkia or the zebrafish Danio rerio (Cvetkovic et al, 2010;Eb-Levadoux et al, 2017;Xu et al, 2014).…”
Section: Living Yeast S Cerevisiae Is Able To Accumulate Umentioning
confidence: 99%